(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
This work aims to be a contribution to understand the dynamics of setting up and supplying the manuscripts in Pomposa during the 11th century. It starts from the historical and paleographic study of the inventory written by Enricus monachus under the government of abbot Girolamo and of the known manuscripts attributable to the Pomposa’s scriptorium and datable to the same period. The aim is to allow the opening of new research paths on the library and on the cultural changes that took place between the Pomposa’s monastery and the other centers of Northern Italy in a period in which these institutions became crucial for the evolution of the Papacy and the Empire.